Distribution of neuropeptides in endocrine and exocrine pancreas of long-legged buzzard (Buteo rufinus): An immunohistochemical study - Bayrakdar, Ali; Yaman, Mine; Atalar, Omer; Tarakci, Berrin Gencer; Ceribasi, Songul (Elsevier Science Bv, 2011)
This study aimed to determine the existence and distribution of certain neuropeptides in endocrine and exocrine pancreas of the long-legged buzzard by using immunohistochemical methods. SOM-14-, NPY- and CGRP-IR endocrine cells were determined in both central and peripheral regions in A-islets within the pancreas, while SP-IR endocrine cells were found only in the central region, and CCK-8- and galanin-IR endocrine cells were only detected in peripheral region. On the other hand, in B-islets; SP-, NPY- and CGRP-IR endocrine cells were determined in both central and peripheral regions, while SOM-14- CCK-8- and galanin-IR endocrine cells were found only in the peripheral region. In addition; SOM-14-, NPY-, CGRP-. CCK-8- and galanin-IR cells were also observed in exocrine pancreas. This distribution pattern in the pancreas of the long-legged buzzard demonstrates that neuropeptides perform their probable affects through endocrine and/or paracrine mechanisms. In conclusion, the existence and distribution of neuropeptides in the pancreas of long-legged buzzard have been introduced in this study for the first time and this bird species has also been found to differ from other types of avian species. (c) 2010 Elsevier B.V. All rights reserved.
Keywords: Neuropeptides; Pancreas; Long-legged buzzards; Immunohistochemistry